COLLABORATIVE GOVERNANCE DALAM PENANGANAN STUNTING DI KOTA PEKANBARU TAHUN 2021-2022 - Trifany, Nadifa; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Stunting is a crucial problem that Indonesia is still facing so it requires steps in its handling efforts. To accelerate the reduction of stunting rates, there needs to be convergence, coordination and cooperation between cross-programs, cross-sectors, community empowerment and all related sectors in an effort to accelerate stunting prevention in Pekanbaru City. Collaborative governance is one of the new strategic models of government that involves various stakeholders or stakeholders together to make joint decisions that aim to solve problems in handling stunting. The purpose of this research is to find out Collaborative Governance in Handling Stunting in Pekanbaru City in 2021-2022. This research uses the theory of collaborative governance proposed by Ansel and Gash, namely starting conditions, institutional design, facilitative leadership, collaboration processes and collaborative governance outcomes. This research method is descriptive research with a qualitative approach. The data sources used are primary and secondary data. The data collection techniques used were interviews and documentation. The results showed that there were various actors involved in Collaborative Governance in Handling Stunting in Pekanbaru City in 2021-2022, such as the Health Office, Population Control and Family Planning Office, the private sector and others. The implementation of collaboration in handling stunting in Pekanbaru City is carried out in several stages, namely starting conditions, institutional design, facilitative leadership, collaboration process and collaborative governance results. This research concludes that the handling of stunting in Pekanbaru City which is carried out with collaboration between the government, the private sector and the community has not been optimally implemented. Because in the collaboration process there are still obstacles in the lack of understanding from the government regarding their roles and duties in collaboration, there is a limited budget to implement stunting handling programs and a lack of public awareness to participate in accelerating stunting reduction, causing an increase in the number of stunting cases in Pekanbaru City. Keywords: Collaborative Governance, Handling, Stunting